AIDS in Haiti: Situating the Incidence and Prevalence of AIDS in Structural Violence - Samra Hasnain (Caribbean Studies Students' Union, 2015)
AIDS in Haiti: Situating the Incidence and Prevalence of AIDS in Structural Violence by Samra Hasnain